The gospel according to St Mark the Greek text with introduction, notes, and indexes - Taylor, Vincent, 1887-1968 (Grand Rapids, MI Baker, 1966)
Includes bibliographical references and indexes
Keywords: Bible. N.T. Mark -- commentaries